2014
DOI: 10.22256/pubvet.v8n14.1750
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades químicas e rendimento da piramutaba (Brachyplastystoma vaillantii, Valenciennes, 1840)

Abstract: ResumoA piramutaba é matéria prima para a indústria pesqueira onde é destinada ao beneficiamento na forma de filé congelado. O presente estudo foi realizado com o objetivo de verificar a determinação do rendimento na indústria e determinar a composição centesimal do filé e do resíduo. Para avaliar a composição centesimal do filé e do resíduo foram adquiridos 20 exemplares, junto aos barcos de pesca, com peso médio de 1093,50 g. Os dados de rendimentos foram calculados na linha de produção das industrias, e tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…In keeping with the yield characteristics in a clean body, L. friderici and A. ocellatus presented the highest and lowest percentages for skin and filet cuts, both in the flood period. Values very close to those reported by this study were observed in mapará (Hypothalamus edentatus) and piramutaba (Brachyplatystoma vaillantii) (Souza & Inhamuns, 2011;Oliveira & Damasceno, 2014), and in matrinxã (Brycon cephalus) (Mujica et al, 2011). L. friderici is a fusiform species and tends to have higher yields because of its cylindrical muscle mass (Contreras-Guzmán, 1994), which can be processed in various ways.…”
Section: Discussionsupporting
confidence: 90%
“…In keeping with the yield characteristics in a clean body, L. friderici and A. ocellatus presented the highest and lowest percentages for skin and filet cuts, both in the flood period. Values very close to those reported by this study were observed in mapará (Hypothalamus edentatus) and piramutaba (Brachyplatystoma vaillantii) (Souza & Inhamuns, 2011;Oliveira & Damasceno, 2014), and in matrinxã (Brycon cephalus) (Mujica et al, 2011). L. friderici is a fusiform species and tends to have higher yields because of its cylindrical muscle mass (Contreras-Guzmán, 1994), which can be processed in various ways.…”
Section: Discussionsupporting
confidence: 90%